KORELASI ANTARA FAKTOR CURAH HUJAN DENGAN KEJADIAN DBD TAHUN 2010-2014 DI KABUPATEN KARANGANYAR - Arifatun Nisaa (Fakultas Kesehatan Masyarakat, Universitas Jember, 2018)
Dengue hemorrhagic fever is still a public health problem and the incidence of the case was up and down erratically. One of the causes of DHF incidence is rainfall. Based on geographic location and topography, Karanganyar Regency has temperature temperature between 180-310C, the lowest temperature is in Tawangmangu Subdistrict when rainy season is 180C, while in Gondangrejo and Colomadu District reaches 310C. Aedes aegypti mosquitoes can survive at a temperature of 22 - 240C. In the rainy season, usually the incidence of dengue cases tends to increase. Based on data from 6 measuring stations in Karanganyar District, the number of rainy days during the year was 115.6 days with an average of 7,231.4 mm rainfall, where the highest rainfall occurred in February to April, while the lowest was at August and September. This study was an observational analytic study with multiple temporal analyzes. Data used in this research are secondary data of DBD case and rainfall factor data. Dengue fever spreads in residential areas. The strength of rainfall correlation with dengue is strong (r = 0.62).There is no significant correlation between rainfall factor and DHF. This may be due to the lack of duration of data taken, incomplete physical factor data and the influence of other dominant factors.